Free-energy barriers in the Sherrington-Kirkpatrick model - Bittner, Elmar; Janke, Wolfhard (epl, 2006)
The Sherrington-Kirkpatrick spin-glass model is investigated by means of Monte Carlo simulations by employing a combination of the multi-overlap algorithm with parallel tempering methods. We investigate the finite-size scaling behaviour of the free-energy barriers which are visible in the probability density of the Parisi overlap parameter. Assuming that the mean barrier height diverges with the number of spins N as , our data show good agreement with the theoretical value .